تأثير المتغيرات السياسية واألمنية في العراق على السياسة الخارجية اإليرانية بعد العام 2003 البحث مستل من رسالة الماجستير - حسن, كمال عبدلله; صالح, جبار محمد (Sulaimani Journal for Humanities, 2022)
The Effect of Political and Security Variables in Iraq on Iranian Foreign Policy after 2011 The study addresses one solution of the most important factors on the regional ground, namely the security variables in Iraq which exert influence on the Iranian foreign policy towards Iraq after 2003. This can be achieved by recognizing the most important principles and objectives of the Iranian foreign policy after 1979, and the effect of the events of September 11, 2001 on the advance of that policy on both internal and regional levels along with the study impact of Iraq’s security variable on Iranian foreign policy, which constitutes a vital ground for it, and how it pursued to exploit the security and political vacuum by using its capabilities to confront the existing American threat in the region. Consequently, Iran exploited Iraq’s new political system institutions after 2005, to exert influence on its political stances. Iran did so by solidifying its relations with all political parties, particularly the Shiite political parties’ alliances to boost its political impact to ensure the new regime continues despite challenges with the aim that it would serve its national interests.